1995
DOI: 10.1097/00005392-199509000-00083
|View full text |Cite
|
Sign up to set email alerts
|

Renal Transplantation in Patients with Posterior Urethral Valves

Abstract: Renal transplantation into a valve bladder is not associated with an abnormally high rate of failure. Deterioration of graft function secondary to lower urinary tract dysfunction is uncommon, with the majority of patients able to use the unmodified native bladder as a receptacle for the transplanted kidney.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…It was hypothesized that this was primarily due to bladder dysfunction. More recent papers have reported that overall success rates for PUV patients are similar to control patients with medical causes for transplant with acknowledgment of the need for aggressive control of bladder function before transplant 2,9,10,17 . Kamal et al reviewed 20 PUV patients from their institution and reported similar graft outcomes when compared to controls.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It was hypothesized that this was primarily due to bladder dysfunction. More recent papers have reported that overall success rates for PUV patients are similar to control patients with medical causes for transplant with acknowledgment of the need for aggressive control of bladder function before transplant 2,9,10,17 . Kamal et al reviewed 20 PUV patients from their institution and reported similar graft outcomes when compared to controls.…”
Section: Discussionmentioning
confidence: 99%
“…When we categorized our patients into those with and without Mitrofanoff (Table 1) Table S1. 2,9,10,17 Kamal et al reviewed 20 PUV patients from their institution and reported similar graft outcomes when compared to controls. They noted that PUV patients were significantly younger at the time of RT; however, their age at presentation for PUV was 5 years suggesting that many of these boys may have already progressed to ESRD by the time of diagnosis.…”
Section: Re Sultsmentioning
confidence: 95%
See 2 more Smart Citations
“…It is well recognized that libido and potency is markedly aCected in survival may be reduced significantly by transplantation into a valve bladder. Eleven large series [37][38][39][40][41][42][43][44][45][46][47], with a adults with chronic renal failure [50]. Thus, it is not unexpected to find problems with sexual function in men total of 184 patients, have examined this issue ( Table 1).…”
Section: Late Complicationsmentioning
confidence: 99%